Belajar Fisika dengan Arduino: Eksperimen Motor DC untuk Memahami Konsep Daya, Momentum, dan Gaya - Jafar, Agustina; Rosita, Sri; Agus, Nurfadillah; Fitrah, Andi Nurul; Satriani, Satriani; Riskawati, Riskawati (Journal Artificial: Informatika dan Sistem Informasi, 2024)
in DC motor experiments to understand the concepts of power, momentum, and force. The urgency of this research lies in the need to bridge the gap between physics theory and practical applications, which can help students better understand abstract physics concepts. This research employs a STEM-based approach that integrates technology and hands-on experiments, where the Arduino Uno acts as the main controller in the experiment. The method used involves a DC motor experiment controlled by Arduino, measuring variables such as voltage, current, and motor speed to analyze the relationship between power, momentum, and system efficiency. The data obtained from this experiment is used to calculate power, momentum, and efficiency, providing insights into the conversion of electrical energy to mechanical energy. The results show that the STEM-based experimental approach with Arduino is effective in enhancing students' understanding of fundamental physics principles and modern technology applications. The use of Arduino enables more accurate measurements and precise control over experimental variables. This study also finds that the experiment can improve students' technical skills in programming and microcontrollers, supporting STEM education.